ANAK DENGAN ALERGI SUSU SAPI - Ade Saifan Surya; Salmiyanti Salmiyanti (STIKes Ibnu Sina Ajibarang, 2023)
Cow's milk allergy is defined as a reproducible adverse reaction to one or more cow's milk proteins (usually casein or serum -lactoglobulin). ASS is a type of food allergy with the highest incidence in children under three years old, where this age is a golden period in the growth and development of a child. The incidence of cow's milk allergy in the world is only 2-3%, but cow's milk allergy is a problematic health problem for children, because in its management children must eliminate cow's milk protein from their daily diet, including replacing formula milk which mostly contains cow's milk protein. . 54% of cow's milk allergy is mediated by IgE, and 46% is not mediated by IgE. IgE-mediated reactions occur within minutes or within an hour of ingestion of cow's milk (rapid reaction). Allergic symptoms associated with IgE reactions include urticaria, diarrhea, eczema, rhinitis, and anaphylaxis. Meanwhile, symptoms associated with non-IgE reactions (slow reactions) such as vomiting, constipation, hemosiderosis, malabsorption, villous atrophy, eosinophilic proctocolitis, enterocolitis, and eosinophilic esophagitis may occur after one hour of consumption of cow's milk.